Insight into luminescence enhancement of coordinated water-containing lanthanide metal–organic frameworks by guest molecules. Issue 5 (17th December 2014) - Wang, Yanlong; Xue, Zhenzhen; Sun, Zhihao; Tan, Chunhong; Wen, Yuehong; Hu, Shengmin; Zhu, Qilong; Sheng, Tianlu; Wu, Xintao
Abstract : The luminescence of novel metal–organic frameworks can be enhanced and reversibly modified by different guest molecules. Abstract : A series of isostructural lanthanide three-dimensional compounds [Ln(HL)(H2 O)2 ]·guest (Ln = Tb or Eu, H4 L = 2-( N, N -bis(4-methylbenzoic acid)amino)benzoic-1, 4-dioic acid, guest = NMP, DMA, DMF or H2 O) were assembled and characterized. Their luminescence intensities and quantum yields increase in the order of the guest molecules: NMP > DMA > DMF > H2 O (NMP = N -methyl-2-pyrrolidone, DMA = N, N -dimethylacetamide, DMF = N, N -dimethylformamide). The investigation reveals that the hydrogen-bond formed between the metal–organic frameworks should be responsible for the luminescence enhancement of the compounds.